2019
DOI: 10.1371/journal.pone.0214023
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial type II NADH dehydrogenase of Plasmodium falciparum (PfNDH2) is dispensable in the asexual blood stages

Abstract: The battle against malaria has been substantially impeded by the recurrence of drug resistance in Plasmodium falciparum , the deadliest human malaria parasite. To counter the problem, novel antimalarial drugs are urgently needed, especially those that target unique pathways of the parasite, since they are less likely to have side effects. The mitochondrial type II NADH dehydrogenase (NDH2) of P . falciparum , PfNDH2 (PF3D7_0915000), has been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…The Cas9 CDS is flanked by an yDHOD (yeast dihydroorotate dehydrogenase) gene on the 5' end and a Flag tag on the 3' end. We previously removed the yDHOD gene from pAIO, yielding a pre-gRNA construct without yDHOD designated pAIO-Cas9-yDHOD(-) (48). In pAIO-Cas9-yDHOD(-), we performed a series of cloning steps to replace BtgZI with EcoRI for cloning gRNAs and modified the trans-activating sequence of the gRNA according to published studies (59,60) to enhance its binding to Cas9 (details in the Supporting Information).…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cas9 CDS is flanked by an yDHOD (yeast dihydroorotate dehydrogenase) gene on the 5' end and a Flag tag on the 3' end. We previously removed the yDHOD gene from pAIO, yielding a pre-gRNA construct without yDHOD designated pAIO-Cas9-yDHOD(-) (48). In pAIO-Cas9-yDHOD(-), we performed a series of cloning steps to replace BtgZI with EcoRI for cloning gRNAs and modified the trans-activating sequence of the gRNA according to published studies (59,60) to enhance its binding to Cas9 (details in the Supporting Information).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Briefly, the progress of a 300 µL of cyt c reductase reaction, which consisted of mitoprep samples (containing bc 1 complex), reduced decylubiquinol (electron donor), oxidized horse heart cytochrome c (electron acceptor) and KCN (inhibiting Complex IV activity) in buffer at pH 7.4, was recorded at 550 nm using the spectrophotometer. Other procedures followed our published studies (36,48).…”
Section: Mitochondrion Preparation (Mito-prep) and Bc 1 Complex Enzymmentioning
confidence: 99%
“…In another study, selection of P. falciparum with putative inhibitors of P. falciparum NADH dehydrogenase 2 (PfNDH2) led to mutations in the more likely target: the parasite cytochrome B gene expressed by the mitochondrial genome (237). Consistent with these findings, deletion of the pfndh2 gene has been shown to be dispensable in asexual blood stages, and further, its deletion does not alter the parasite's susceptibility to multiple mitochondrial electron transport chain (mtETC) inhibitors (241).…”
Section: Figmentioning
confidence: 91%
“…Complex II and MQO are components of the TCA cycle, and NDH-2 is required to re-oxidize NADH produced in mitochondrial metabolism, including the TCA cycle. Genetic validation conducted using P. berghei-infected mice or cultured P. falciparum has shown that NDH-2 [9,10] and complex II [11,12] are essential for oocyst development inside the mosquito, while MQO is required (at minimum) in the asexual blood stage [7,13]. Little is known about the role of G3PDH in apicomplexan parasites, although some studies have suggested a role for G3PDH in redox-balance, gluconeogenesis, and lipid biosynthesis [14,15].…”
Section: Introductionmentioning
confidence: 99%